Which Quality does make the Difference in Cochlear-implant Therapy? - Stöver, Timo; Leinung, Martin; Loth, Andreas (Laryngo-Rhino-Otologie, 2020)
Since its introduction, cochlear implantation has seen an uptake and development which could not have been anticipated. Not only have the technical possibilities seen significant change but also the range of indication. Examples include the care of very young or very old patients, bilateral implantation or the use of residual hearing for combined electric-acoustic stimulation (EAS). This development is very dynamic, offering tremendous opportunities for hearing rehabilitation of affected patients. At the same time, however, it places considerable demands on service providers to ensure the care provided is striving to be of optimal quality. In recent years, an intensive discussion has taken place with the aim of defining quality parameters to serve as the cornerstones of cochlear implant (CI) treatment. These were initially based on the description of a defined course of a cochlear implantation and thus on the partial aspects of process, structure and result quality for quality assurance. Practical implementation of these considerations then resulted among other things in the “White Paper CI Care” and the concept of a “National CI Registry” of the DGHNOKHC. In addition to a content-oriented discussion within the professional society of the DGNHNOKHC, other parties like health insurers as payers are also beginning to show interest in influencing the process of CI care (e. g. QuInCI initiative by Techniker Krankenkasse). The legislator is also preparing measures that will directly affect CI care (“Implant Registry Act”). This article will present the current state of knowledge in quality assurance of CI care and define Germany’s position compared to other countries.
Keywords: Cochlear Implant; Quality Control; Standardisation